Survival, disease progression and prognostic factors in elderly patients with mycosis fungoides and Sézary syndrome: a retrospective analysis of 174 patients. (25th September 2018) - Lebowitz, E.; Geller, S.; Flores, E.; Pulitzer, M.; Horwitz, S.; Moskowitz, A.; Kheterpal, M.; Myskowski, P.L.
Abstract: Background: Advanced age at diagnosis is considered a poor prognostic factor in mycosis fungoides (MF) and Sézary syndrome (SS). Objective: To evaluate the outcomes and prognostic factors in patients diagnosed at an advanced age (≥65 years) with MF/SS. Methods: Survival, progression rates and various clinical and histopathological variables were studied in a group of 174 elderly patients diagnosed with MF/SS between 1992 and 2015 at a single referral cancer center in the United States. Kaplan–Meier estimates were used to determine survival and progression and Cox proportional hazards regression univariate and multivariate models were used to identify prognostic factors. Results: Of 174 elderly patients, 76.4% were diagnosed with early‐stage (clinical stages IA‐IIA) and 23.6% with late‐stage MF/SS (IIB‐IV). Advanced age was associated with poor overall survival, but not with disease‐specific survival (DSS) or progression‐free survival (PFS). Gender, increasing clinical stage, T and B classifications, elevated lactate dehydrogenase (LDH) levels and development of large cell transformation (LCT) were significant predictors of poor survival or disease progression. Patients with early‐stage MF and <10% total skin involvement (T1 classification) or patch‐only disease (T1a/T2a) showed better PFS with no observed disease‐specific mortality. Folliculotropic MF was associated with poor DSS in patients with early‐stage disease. Conclusions: Older age at diagnosis of MF/SS does not predict worse disease‐specific outcomes. Elderly patients with early‐stage disease, specifically involving less than 10% of the skin surface with patches but without plaques or folliculotropism, have an excellent prognosis. However, the development of LCT is a strong prognostic indicator of poor survival in elderly patients with MF/SS.